Pengaruh ekstrak krim Morinda citrifolia terhadap jumlah fibroblas pada penyembuhan luka tikus Wistar - Vania Lannisa Haestidyatami; I Wayan Sugiritama; Ni Made Linawati (DiscoverSys Inc., 2019)
Introduction. Wound healing is a complex biological process involving four stages, i.e., hemostasis, inflammation, proliferation, and remodeling. In the proliferation phase, there is an increase in the number of fibroblas cells. Morinda citrifolia is a fruit that contains the antioxidant compound, Quercetin. These antioxidant properties are thought to be able to accelerate the process of wound healing through the process of modulating the oxidative process and improving skin microstructure. The relationship of Quercetin to fibroblas cells which plays an essential role in the proliferation phase is not yet fully known. This study was conducted to determine the effect of Morinda citrifolia extracts on the number of fibroblas cells during the process of wound healing in Wistar rats.Method. Experimental, post-test with control group study was conducted using 24 rats divided into four groups. In group I, rats were treated with incisions and given a Placebo cream, groups II, III and IV were given incisions and cream containing ethanol extract of Morinda citrifolia 5%, 10%, and 20% respectively. The number of fibroblass was calculated using the digital analysis method using Image Raster 3 Software. The number of fibroblas cells was calculated as the percentage of fibroblas cells seen in the field of view. Data analysis conducted with the One-Way ANOVA and Post-Hoc LSD test.Results. The control group had an average number of fibroblas cells 23.3% ± 1.9%. The mean fibroblas cells in the intervention group with extracts of 5%, 10%, 20% were 27.6% ± 6.7%, 38.3% ± 8.8% and 22.3% ± 2.7%, respectively. The ANOVA test results showed a significant difference in the number of fibroblass between treatment groups (p<0.001). Post-hoc LSD test shown that only the treatment group with 10% extract showed a difference in the average number of fibroblas cells compared to the other groups.Conclusion. The highest number of fibroblas cells was found in the treatment group with 10% extract.